Phase composition in NiTi near-surface layers after electron beam treatment and its variation depending on beam energy density - Ostapenko M. G. Marina Gennadievna; Meisner L. L. Ludmila; Lotkov A. I. Aleksandr; Gudimova E. Y. Ekaterina (2014, 2014)
Title screen